2020
DOI: 10.1111/jcmm.16099
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of partial epithelial mesenchymal transition‐related genes in hepatocellular carcinoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…A total of 298 potential lncRNA candidates with miRNA-29c-binding sites were predicted ( Supplementary Table S2 ). Considering the ceRNA hypothesis that the relevance between lncRNA and miRNA was negative while the relevance between lncRNA and mRNA was positive ( Lei et al, 2021 ), we firstly performed a correlation analysis between miRNA-29c and the 298 lncRNAs in 372 STAD samples of TCGA databases. Among them, only 33 lncRNA–miRNA pairs were inversely related ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 298 potential lncRNA candidates with miRNA-29c-binding sites were predicted ( Supplementary Table S2 ). Considering the ceRNA hypothesis that the relevance between lncRNA and miRNA was negative while the relevance between lncRNA and mRNA was positive ( Lei et al, 2021 ), we firstly performed a correlation analysis between miRNA-29c and the 298 lncRNAs in 372 STAD samples of TCGA databases. Among them, only 33 lncRNA–miRNA pairs were inversely related ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…We also predicted the upstream lncRNAs of miRNA-29c in gastric cancer. Based on the ceRNA hypothesis that the relevance between lncRNA and miRNA was negative, while the relevance between lncRNA and mRNA was positive ( Zhou et al, 2020 ; Lei et al, 2021 ), nine lncRNAs were considered for following analyses. Further expression analysis and survival analysis showed that only HIF1A-AS2 and RP11-366L20.2 fulfilled our criteria that they are highly expressed in tumors and that their high expression indicates a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, partial EMT (p-EMT) can drive distinct migratory properties and enhance the epithelialmesenchymal plasticity of cancer cells and cell fate plasticity. 67 Yu et al 68 suggested that key p-EMT-related genes (P4HA2, ITGA5, MMP9, MT1X, and SPP1) could serve as prognostic biomarkers and therapeutic targets for HCC. Recent studies have demonstrated the role of exosomes in EMT progression in different types of cancer, including HCC.…”
Section: Role Of Exosomes In the Formation Of Hcc Microenvironmentmentioning
confidence: 99%
“…EMT-associated gene models have been developed to predict HCC prognosis [ 4 , 12 ]. However, the functions and prognostic value of EMT-related lncRNAs have not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%